Erratum - da Silva, Anderson Lima Cordeiro; dos Santos, Gustavo Gonçalves; do Nascimento, Edson Silva; de Oliveira Júnior, Ronaldo Eustáquio (Brazilian Journal of Sexually Transmitted Diseases, 2024)
*